Governing the gaps in water governance and land-use planning in a megacity: The example of hydrological risk in Mexico City. (31st December 2018) - Lerner, Amy M.; Eakin, Hallie C.; Tellman, Elizabeth; Bausch, Julia Chrissie; Hernández Aguilar, Bertha
Abstract: Megacities are socio-ecological systems (SES) that encompass complex interactions between residents, institutions, and natural resource management. These interactions are exacerbated by climate change as resources such as water become scarce or hazardous through drought and flooding. In order to develop pathways for improved sustainability, the disparate factors that create vulnerable conditions and outcomes must be visible to decision-makers. Nevertheless, for such decision-makers to manage vulnerability effectively, they need to define the salient boundaries of the urban SES, and the relevant biophysical, technological, and socio-institutional attributes that play critical roles in vulnerability dynamics. Here we explore the problem of hydrological risk in Mexico City, where vulnerabilities to flooding and water scarcity are interconnected temporally and spatially, yet the formal and informal institutions and actors involved in the production and management of vulnerability are divided into two discrete problem domains: land-use planning and water resource management. We analyze interviews with city officials working in both domains to understand their different perspectives on the dynamics of socio-hydrological risk, including flooding and water scarcity. We find governance gaps within land-use planning and water management that lead to hydro-social risk, stemming from a failure to address informal institutions that exacerbate vulnerability to flooding and water scarcity. Mandates in both sectors are overlapping and confusing, while socio-hydrological risk is externalized to the informal domain, making it ungoverned. Integrated water management approaches that recognize and incorporate informality are needed to reduce vulnerability to water scarcity and flooding. Highlights: We discuss the perceptions of government officials in land-use and water management sectors regarding the framing of hydrological risk in Mexico City. There is a gap in governance between the two sectors related to hydrological risk, especially given formal and informal urban growth. The water management sector tends to see the problem through the lens of infrastructure, and the land-use sector sees it as one of informal urban growth. Neither sector claims responsibility for governing hydrological risk, particularly related to informality, which is perceived as an ungovernable process.